DOI: 10.22215/etd/2020-14021
|View full text |Cite
|
Sign up to set email alerts
|

Examining Trajectories of Change on Risk and Protective Factors among White and Black Men Offenders on Community Supervision in Iowa

Abstract: Relying on the results of validated risk assessments is vital to evidence-based decision making in corrections. Advancements in the approach to risk assessment has seen an emphasis on measuring dynamic risk factors alongside protective factors, as both are expected to be useful for identifying treatment targets and measuring changes in risk over time. Despite these advancements, empirical evidence of change on dynamic risk and protective factors remains limited. Utilizing a sample of 3,976 White and Black men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 136 publications
0
7
0
Order By: Relevance
“…Following previous studies (Chadwick, 2020;Davies et al, 2022;Lloyd, Hanson et al, 2020), we used a threefactor structure for DRAOR within the ESEM analyses. For ordinal categorical data with less than five categories, weighted least squares estimation methods with robust corrections are more appropriate than maximum likelihood methods (see Sellbom & Tellegen, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following previous studies (Chadwick, 2020;Davies et al, 2022;Lloyd, Hanson et al, 2020), we used a threefactor structure for DRAOR within the ESEM analyses. For ordinal categorical data with less than five categories, weighted least squares estimation methods with robust corrections are more appropriate than maximum likelihood methods (see Sellbom & Tellegen, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Corrections agencies in other countries use DRAOR (e.g., see Chadwick, 2020;K. Singh & Samion, 2016), but most current DRAOR research originated from Aotearoa NZ and, thus, these samples contain substantive M aori participants (e.g., see Lloyd, Hanson et al, 2020;Polaschek & Yesberg, 2017;Scanlan et al, 2020;.…”
Section: Aotearoa Nz Contextmentioning
confidence: 99%
“…12 For example, the DRAOR Total score has been strongly correlated with the Stable (r = .87 to .92), Acute (r = .81 to .87), and Protective subscales (r = -.82 to -.89; Averill, 2016;Ferguson, 2015;Muirhead, 2016;Perley-Robertson, 2018;Smeth, 2013). Additionally, the DRAOR Stable and Acute subscales have been consistently found to be moderately to strongly positively correlated (r = .46 to .73), indicating that the two subscales measure similar constructs (i.e., criminogenic risk; Averill, 2016;Chadwick, 2014;Chadwick, 2020;Ferguson, 2015;Muirhead, 2016;Perley-Robertson, 2018;Smeth, 2013;Tamatea & Wilson, 2009;Wardrop, 2020).…”
Section: Evidence Of Draor Validitymentioning
confidence: 94%
“…Research has shown that DRAOR scores are normally distributed and demonstrate change over the course of supervision (Chadwick, 2020;Lloyd et al, 2020a;Tamatea & Wilson, 2009). However, previous investigations into the DRAOR's internal consistency, a common indicator of scale reliability that measures whether a series of items have been appropriately grouped based on their interrelatedness, have yielded consistently mixed results.…”
Section: Evidence Of Draor Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation